6u+4u-(-6u)-15u-6=9

Simple and best practice solution for 6u+4u-(-6u)-15u-6=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6u+4u-(-6u)-15u-6=9 equation:


Simplifying
6u + 4u + -1(-6u) + -15u + -6 = 9

Remove parenthesis around (-6u)
6u + 4u + -1 * -6u + -15u + -6 = 9

Multiply -1 * -6
6u + 4u + 6u + -15u + -6 = 9

Reorder the terms:
-6 + 6u + 4u + 6u + -15u = 9

Combine like terms: 6u + 4u = 10u
-6 + 10u + 6u + -15u = 9

Combine like terms: 10u + 6u = 16u
-6 + 16u + -15u = 9

Combine like terms: 16u + -15u = 1u
-6 + 1u = 9

Solving
-6 + 1u = 9

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 1u = 9 + 6

Combine like terms: -6 + 6 = 0
0 + 1u = 9 + 6
1u = 9 + 6

Combine like terms: 9 + 6 = 15
1u = 15

Divide each side by '1'.
u = 15

Simplifying
u = 15

See similar equations:

| 1/8y=-17 | | 2(3-4x)=3(2x+5) | | 2.4x+11.3=3.7-0.6 | | 26(x-2)+3(4-x)=25 | | 0.75x+13.25=1.25x+12 | | 7x+2x+4x-10x-x=20 | | (2.4x)+11.3=3.7-(0.6x) | | 70-2x=210-42x | | -2x-2(3x+5)=-106 | | 2x^2+25x-3=0 | | X-4(2X-3)=26 | | 2x^2=82 | | 2=2.27-s-4 | | .09n=600-0.12n+198 | | X-4(2X-30)=26 | | -2x-4(-6-10)=-136 | | 5u+11=111 | | 6n+24= | | 67-2x=83-3x | | 0.22m=0.1m+15.60 | | (5x^3y/20xy^5)^4 | | 13X=-X^2-12 | | (12x+7)+(3x^2-12x-5)= | | 3x^2-32x+75=0 | | 26x-2=8x+3+85 | | 502.08+1.6= | | -20=1/3n--10 | | -4+2v=4(v-4) | | 2x+6+3x=7+2x+8 | | 5z+8z=Z-2-9z | | 10=5+v | | 8x+9=6x+32 |

Equations solver categories